SIMPLE BREAST CYST WITH AN ATYPICAL OUTCOME - Oliveira Junior, Idam de; Mendes, Talita Aparecida Riegas; Watanabe, Anapaula Uema Hidemi; Silva, Vinicius Duval da; Vieira, Rene Aloisio da Costa (Mastology, 2020)
Introduction: Squamous cell carcinoma is a malignant neoplasm of epidermal keratinocytes, which rarely affects the breast, representing 0.1% to 2% of all types of breast cancer, and belonging to the heterogeneous group of metaplastic breast carcinomas. Clinically, it is associated with large tumors, tending toward cystic degeneration, with skin invasion and ulceration, and no specific radiological characteristics. It is also associated with a proliferative nature (Ki67) and triple--negative tumors. The prognosis is bleak, with a mean 5-year survival of 50% to 63%. Case report: A female patient, 37 years old, receiving palliative chemotherapy for stage IV endocervical adenocarcinoma (pT3 pN1 M1 – pleura) complained of a tumor in her left breast, with growth in the prior month. Physical examination revealed a palpable, mobile tumor in the central region of the left breast, measuring 11x9.5 cm, and with soft consistency. Mammography identified a regular, well-defined nodule in the left breast (BI-RADS 0). Breast ultrasound (BUS) indicated a simple cyst, with thin and regular walls, without a solid parietal component, measuring 7.6x5.2x4.3 cm. She underwent a BUS-guided relief biopsy of the cys-tic lesion with total removal of the lesion. Twenty days later, local recurrence occurred, and the lesion was drained again. Culture and cytology were negative for malignancy. She continued receiving chemotherapy. Eight months after the onset of symptoms, at the end of chemotherapy, and with no palpable lesion in the left breast, BUS revealed a simple 2.6 cm cyst, with no sign of flow on the Doppler study, and the patient was submitted to excision of cystic lesion guided by radio-guided occult lesion localization (ROLL). Anatomopathological results indicated triple-negative metaplastic carcinoma, measuring 2.7 cm, with squamous differentiation and free surgical margins. Sentinel lymph node biopsy in the left axilla showed two lymph nodes free of neoplastic involvement. Adjuvant treatment consisted of FAC chemotherapy and hypo-fractionated radiotherapy. Currently, at 18 months of follow-up, she has no evidence of recurrence. Conclusion: Simple breast cysts are benign lesions, with active surveillance, except in the case of recurrence, residual mass after relief biopsy, or presence of bloody fluid in the biopsy material. This report describes a rare case of metaplastic carcinoma, which must be remembered as a differential diagnosis in recurrent breast cyst.